People with special needs in contemporary Saudi families – A qualitative study with a suggested guidance program – - Alsunady, Khulud Ebrahim; Almutairi, Alkhansa Awad; Linjawi, Badia Hassan Mohamed (Journal of Humanities & Social Sciences, 2021)
The study mainly targeted tracking the life of the handicapped who hold an "Autism" disease in the modern Saudi family, and identifying the pros and cons of each of these handicapped, the descriptive and analytical approach was used. Data were collected by observing the cohabitation and the interview newspaper, and a sample consisting of 16 mothers (8 of 8 Females (with autism), and mothers (8 males) with autism in each of the city of Jeddah, the city of Taif, and the city of Jizan in the Kingdom of Saudi Arabia. The sample was withdrawn randomly. Among the most important findings of the study on childhood: comprehensive rehabilitation programs played a key role in helping autistic children and their families, and it showed the lack of independence in the autistic child, the lack of social status for autistic children among their relatives and companions, and that children with autism suffer from difficulties Daily challenges, and the most important results for adolescence: The teenager with autism suffers from difficulty mixing with the family, and the presence of difficulty dealing with the teenager in sexual arousal, and the teenager with autism did not gain social status by those around him, and the most important results of the stage of youth: not to adopt the young man himself and the lack of interest in personal hygiene, there is a shortage in the number of institutions and centers that provide care, education and rehabilitation of young autistic, and the lack of family desire of young autistic marriage, The study recommended the need to train an autistic child on independence and interest in education by the family and educational institutions, and the importance of educating mothers on the importance of dealing with the stage of adolescence, and the need to take care of the autistic youth category and deal with them, especially with regard to their personal lives.